Factors affecting Japanese retirees' healthcare service utilisation in Malaysia: a qualitative study. Issue 3 (22nd March 2016) - Kohno, Ayako; Nik Farid, Nik Daliana; Musa, Ghazali; Abdul Aziz, Norlaili; Nakayama, Takeo; Dahlui, Maznah
Abstract : Objective: While living overseas in another culture, retirees need to adapt to a new environment but often this causes difficulties, particularly among those elderly who require healthcare services. This study examines factors affecting healthcare service utilisation among Japanese retirees in Malaysia. Design: We conducted 6 focus group discussions with Japanese retirees and interviewed 8 relevant medical services providers in-depth. Guided by the Andersen Healthcare Utilisation Model, we managed and analysed the data, using QSR NVivo 10 software and the directed content analysis method. Setting: We interviewed participants at Japan Clubs and their offices. Participants: 30 Japanese retirees who live in Kuala Lumpur and Ipoh, and 8 medical services providers. Results: We identified health beliefs, medical symptoms and health insurance as the 3 most important themes, respectively, representing the 3 dimensions within the Andersen Healthcare Utilisation Model. Additionally, language barriers, voluntary health repatriation to Japan and psychological support were unique themes that influence healthcare service utilisation among Japanese retirees. Conclusions: The healthcare service utilisation among Japanese retirees in Malaysia could be partially explained by the Andersen Healthcare Utilisation Model, together with some factors that were unique findings to this study. Healthcare service utilisation among Japanese retirees in Malaysia could be improved by alleviating negative health beliefs through awareness programmes for Japanese retirees about the healthcare systems and cultural aspects of medical care in Malaysia.